How to define the scope of an application development outsourcing through a software factory model?: A systematic review of the literature - Azabache, Albert (2022)
Software development outsourcing is a frequent practice, a widely used modality is the software factory (SWF) model, by which a company hires one or more specialized companies, for a considerable period, to take care of its software development need, both to create new software systems and maintain the existing ones; The model provides important advantages to the contracting organization, but its implementation requires rigorous planning to correctly define the scope of outsourcing, and an adequate implementation plan, among other fundamental aspects. In this article, a systematic review of the literature has been carried out to identify and analyze models, frameworks, guides, or other contributions that propose a way to define the scope of outsourcing that uses the SWF model or similar. We found few studies that address this issue and these only do so tangentially, considering its implementation, but only recommending generic practices to achieve it. Here there is a space to be filled with future works that propose specific recommendations, especially in the technical aspects to be considered.